Epistemic Decolonization as Overcoming the Hermeneutical Injustice of Eurocentrism - Posholi, Lerato (Philosophical Papers, 2020)
This paper is broadly concerned with the question of what epistemic decolonization might involve. It is divided into two parts. The first part begins by explaining the specifically epistemic problem to which calls for epistemic decolonization respond. I suggest that calls for decolonization are motivated by a perceived epistemic crisis consisting in the inadequacy of the dominant Eurocentric paradigm to properly theorize our modern world. I then discuss two general proposals, radical and moderate, for what epistemic decolonization might involve. In the second part, I argue that the inadequacy of Eurocentric epistemic resources constitutes a hermeneutical injustice caused by an irreducible form of epistemic oppression. I then argue that addressing this form of epistemic oppression requires thinking ‘outside’ of the Eurocentric paradigm because the paradigm might fail to reveal and address the epistemic oppression sustaining it. This lends further plausibility to the radical proposal that epistemic decolonization must involve thinking from ‘outside’ the Eurocentric paradigm, but also accommodates the moderate proposal that adopting critical perspectives on Eurocentric thought is an important part of epistemic decolonization.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; décolonisation épistémique; fem9000; féminisme décolonial; injustices herméneutiques; injustices épistémiques; philosophie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

The Institution of Gender-Based Asylum and Epistemic Injustice: A Structural Limit - Sertler, Ezgi (Feminist Philosophy Quarterly, 2018)
One of the recent attempts to explore epistemic dimensions of forced displacement focuses on the institution of gender-based asylum and hopes to detect forms of epistemic injustice within assessments of gender related asylum applications. Following this attempt, I aim in this paper to demonstrate how the institution of gender-based asylum is structured to produce epistemic injustice at least in the forms of testimonial injustice and contributory injustice. This structural limit becomes visible when we realize how the institution of asylum is formed to provide legitimacy to the institutional comfort the respective migration courts and boards enjoy. This institutional comfort afforded to migration boards and courts by the existing asylum regimes in the current order of nation-states leads to a systemic prioritization of state actors’ epistemic resources rather than that of applicants, which, in turn, results in epistemic injustice and impacts the determination of applicants’ refugee status.
Keywords: approches et analyses; capitalisme; confort institutionnel; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; institutions; migration; philosophie; politiques migratoires; racisme; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences